Relation of Vigorous Exercise to Risk of Atrial Fibrillation - Aizer, Anthony; Gaziano, J. Michael; Cook, Nancy R.; Manson, Joann E.; Buring, Julie E.; Albert, Christine M. (The American journal of cardiology, 2009)
Limited data suggest that athletes may have a higher risk of developing atrial fibrillation (AF); however, there has been no large prospective assessment of the relation between vigorous exercise and AF. Logistic regression analyses stratified by time were used to assess the association between frequency of vigorous exercise and risk of developing AF in 16,921 apparently healthy men in the Physicians' Health Study. During 12 years of follow-up, 1,661 men reported developing AF. With increasing frequency of vigorous exercise (0, 1, 1 to 2, 3 to 4, 5 to 7 days/week), multivariate relative risks for the full cohort were 1.0 (referent), 0.90, 1.09, 1.04, and 1.20 (p = 0.04). This risk was not significantly increased when exercise habits were updated or in models excluding variables that may be in the biological pathway through which exercise influences AF risk. In subgroup analyses, this increased risk was observed only in men <50 years of age (1.0, 0.94, 1.20, 1.05, 1.74, p <0.01) and joggers (1.0, 0.91, 1.03, 1.30, 1.53, p <0.01), where risks remained increased in all analyses. In conclusion, frequency of vigorous exercise was associated with an increased risk of developing AF in young men and joggers. This risk decreased as the population aged and was offset by known beneficial effects of vigorous exercise on other AF risk factors.